Discourse and Digital Practices Doing discourse analysis in the digital age - Jones, Rodney H; Chik, Alice; Hafner, Christoph A (Taylor & Francis, 2015)
Discourse and Digital Practices shows how tools from discourse analysis can be used to help us understand new communication practices associated with digital media, from video gaming and social networking to apps and photo sharing. This cutting-edge book: draws together fourteen eminent scholars in the field including James Paul Gee, David Barton, Ilana Snyder, Phil Benson, Victoria Carrington, Guy Merchant, Camilla Vasquez, Neil Selwyn and Rodney Jones answers the central question: "How does discourse analysis enable us to understand digital practices?" addresses a different type of digital media in each chapter demonstrates how digital practices and the associated new technologies challenge discourse analysts to adapt traditional analytic tools and formulate new theories and methodologies examines digital practices from a wide variety of approaches including textual analysis, conversation analysis, interactional sociolinguistics, multimodal discourse analysis, object ethnography, geosemiotics, and critical discourse analysis. Discourse and Digital Practices will be of interest to advanced students studying courses on digital literacies or language and digital practices.